Serbian - Stjepanović, Mihailo (Medical Research, 2023)
AbstractThe year 2022 marked 100 years of modern Serbian pulmonology and 90 years of the Clinic of Pulmology, University Clinical Center of Serbia. This paper presents a concise history of the development of the Clinic, which includes the establishment of the clinic, organizational and educational development, as well as the most prominent directors who made it possible. Also, the current activities of the clinic and the current state of the employees are also described. The aim of the paper is to show the development of the Clinic for Pulmonology, and thus to acknowledge its predecessors and contemporaries.Key words: pulmonology, history, Serbia
Keywords: Serbian